Rational Frenzies and Crashes. - Bulow, J; Klemperer, P (1994)
Most markets clear through a sequence of sales rather than through a Walrasian auctioneer. Because buyers can decide whether to buy now or later, rather than only now or never, their current 'willingness to pay' is much more sensitive to price than the demand curve is. A consequence is that markets will be extremely sensitive to new information, leading to both 'frenzies,' in which demand feeds on itself, and 'crashes,' in which price drops discontinuously. The paper also shows how a result from static auction theory, the revenue equivalence theorem, can be applied to solve for a dynamic price path.